Intra-abdominal multifocal desmoplastic small round cell tumor: a case report of a rare neoplasm - Aregala, Praneeth; Gowda, Sreehari; Marda, Sachin; Kelkeri, Manjula Vijayanand; Jyoshna, T. M. (International Surgery Journal, 2025)
Desmoplastic small round cell tumour (DSRCT) is a rare, highly aggressive malignancy predominantly affecting adolescents and young adults. We report a case of multifocal DSRCT in a 31-years-old male who presented with complaints of abdominal pain, early satiety, weight loss for two months. Whole body 18FDG-PETCT scan revealed FDG avid lesions in the left hypochondrium and lumbar region abutting the stomach, splenic surface, right costophrenic and abdominopelvic lymph nodes, bilateral iliac fossa and in the pelvis. Ultrasound-guided biopsy of the left hypochondriac lesion done. Based on histopathological and immunohistochemical investigations, it was diagnosed to be a DSRCT with multifocal presentation. Patient received adjuvant chemotherapy with VAC/IE, post chemotherapy tumour response was suboptimal, so patient underwent cytoreductive surgery and HIPEC therapy. Despite advances in multimodal therapy, outcomes remain poor since the majority of patients present disease recurrence and die within three years. The dismal survival makes DSRCT an orphan disease with an urgent need for new drugs.